La banca y la sustentabilidad: Una aproximación teórica (Banking and sustainability: A theoretical approach) - Sanchez, Laura; Perez, Felipe (UANL. Facultad de Contaduría Pública y Administración, 2013)
Abstract. The aim of this paper is to present the main theoretical positions in relation with the responsibilities of the financial institutions, regarding the environmental sustainability, as well as the key trends and international recommendations in this matter; with the purpose to answer the research question: Which is the theoretical framework that support the better practices of the banking institutions in the management of their environmental responsibilities? On the basis that these institutions have specific social impacts, related to the effects of the banking products and services in the economical, social and environmental fields, which exceed the typical activities of the financial institutions. For this reason, different initiatives have been proposed in order to encourage that the banking activities fulfill requirements of sustainability, emphasizing that in this sense, the voluntary initiatives have been more relevant than the mandatory regulations. Resumen. El objetivo de este trabajo es exponer las principales posturas teóricas acerca de la responsabilidad de las instituciones bancarias en cuanto a la sustentabilidad del medio ambiente, así como las tendencias predominantes y recomendaciones internacionales sobre este aspecto; buscando contestar a la pregunta: ¿Cuál es el marco teórico que sustenta las mejores prácticas de la banca en cuanto al manejo de sus responsabilidades ambientales? Partiendo de que estas instituciones tienen impactos sociales muy particulares, que se refieren al efecto de los productos y servicios bancarios en los ámbitos económicos, sociales y ambientales que sobrepasan las actividades propias de las instituciones financieras. Por esta razón, se han propuesto distintas iniciativas para propiciar que las actividades bancarias se apeguen a criterios de sustentabilidad, destacando que en este sentido han cobrado mayor relevancia las iniciativas voluntarias que la regulación gubernamental.